The Effect of Work Discipline on Employee Performance at Sadara Resort - Ni Komang Yuni Pratiwi; Nyoman Gede Mas Wiartha; Kadek Andita Dwi Pratiwi; Ni Desak Made Santi Diwyarthi (Westscience Press, 2026)
The hospitality industry relies heavily on the quality of its human resources to deliver excellent service and maintain customer satisfaction. Employee performance is one of the primary determinants of organizational success, while work discipline serves as a fundamental factor influencing employees' ability to perform effectively. This study aims to analyze the effect of work discipline on employee performance at Sadara Resort. A quantitative research approach was employed using a simple linear regression model. Data were collected from 84 employees representing eleven operational departments through structured questionnaires. Prior to hypothesis testing, the research instruments were examined using validity and reliability tests. The findings indicate that all questionnaire items were valid, with correlation coefficients ranging from 0.816 to 0.913, while both variables demonstrated excellent reliability with Cronbach's Alpha values of 0.947. Descriptive analysis revealed that work discipline achieved a mean score of 3.74 and employee performance obtained a mean score of 3.50, both categorized as good. The hypothesis testing results showed that work discipline has a positive and statistically significant effect on employee performance (t = 13.152; p < 0.001). Furthermore, the coefficient of determination (R² = 0.678) indicates that work discipline explains 67.8% of the variation in employee performance, while the remaining 32.2% is influenced by other variables not examined in this study. The findings support Goal Setting Theory, suggesting that employees who consistently comply with organizational rules, demonstrate responsibility, and effectively manage their working time tend to achieve higher levels of performance. The study recommends strengthening supervisory practices, reinforcing Standard Operating Procedures (SOPs), conducting regular employee briefings, and improving time management to further enhance employee performance and service quality in the hospitality industry.